Ji'alah as a Performance-Based Payroll Method: An Analysis of Implementation in Sharia Companies - Intan Purnama Sari; Miti Yarmunida; Nenan Julir (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2024)
Background: Although rental transactions are generally categorized as ijarah, some contemporary practices, such as competitions, app-based transportation, and lost-item retrieval services, are more accurately categorized as ji'alah. Therefore, an in-depth study of the application of the ji'alah contract in the business world, particularly in Sharia companies, is necessary. Method: This research used a qualitative approach with a literature review. Data were collected through literature review and interviews, with data analysis utilizing source and technique triangulation. Informants were selected using non-purposive sampling. Results: The study found that the ji'alah contract has been implemented in various sectors, such as transportation (vehicle rentals, online motorcycle taxis), design competitions, and lost-item retrieval services. The valid conditions for a ji'alah contract include: (1) the parties to the contract must be of sound mind and mature, (2) the wages must be clear in amount and type, (3) the work being paid must be permissible (permissible according to sharia), and (4) it must not contain any prohibited elements of gharar. In practice, ji'alah is more flexible than ijarah because it does not require predetermined time and work details. Conclusion: The ji'alah contract is a sharia-compliant alternative to a results-based wage system that aligns with Islamic economic principles. Its application in various sectors demonstrates that ji'alah can be a solution in modern transactions that prioritize flexibility and fairness. However, its implementation must still comply with Islamic law to avoid gharar or unclear rights and obligations of the parties.